2008
DOI: 10.1099/mic.0.2007/015057-0
|View full text |Cite
|
Sign up to set email alerts
|

Age-related genotypic and phenotypic differences in Moraxella catarrhalis isolates from children and adults presenting with respiratory disease in 2001–2002

Abstract: Moraxella catarrhalis is generally associated with upper respiratory tract infections in children and lower respiratory tract infections in adults. However, little is known regarding the population biology of isolates infecting these two age groups. To address this, a population-screening strategy was employed to investigate 195 worldwide M. catarrhalis isolates cultured from children (,5 years of age) and adults (.20 years of age) presenting with respiratory disease in the years [2001][2002]. Parameters compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
68
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 39 publications
13
68
2
Order By: Relevance
“…However, complement-evading systems, e.g. via OMV-mediated protection, may also play a significant role.Genotypic analysis revealed a high degree of diversity in colonizing M. catarrhalis isolates, an observation which is in agreement with previous studies showing that genotypic heterogeneity is typical of worldwide M. catarrhalis isolates colonizing both children and adults (Hays et al, 2003;Verhaegh et al, 2008;Wolf et al, 2000). Also, no significant association between genotype (cluster) and season, or year of isolation was observed, which is in contrast with a previous publication by Levy et al (2009) relatively confined hospital setting (Levy et al, 2009), whereas the focus of our study was related to community transmission.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…However, complement-evading systems, e.g. via OMV-mediated protection, may also play a significant role.Genotypic analysis revealed a high degree of diversity in colonizing M. catarrhalis isolates, an observation which is in agreement with previous studies showing that genotypic heterogeneity is typical of worldwide M. catarrhalis isolates colonizing both children and adults (Hays et al, 2003;Verhaegh et al, 2008;Wolf et al, 2000). Also, no significant association between genotype (cluster) and season, or year of isolation was observed, which is in contrast with a previous publication by Levy et al (2009) relatively confined hospital setting (Levy et al, 2009), whereas the focus of our study was related to community transmission.…”
supporting
confidence: 79%
“…All isolates negative for both uspA2 and uspA2H genes were tested using primers uspA2end.f and uspA2end (Verhaegh et al, 2008), which amplify a conserved region found at the 39-end of both uspA2 and uspA2H genes.…”
mentioning
confidence: 99%
“…To identify the 16S rRNA types of individual M. catarrhalis isolates, 16S rRNA PCR products were digested using the enzymes FspBI (10 U) and HhaI (10 U) according to Verhaegh et al (2008) [19]. seconds during the first 12 hours, followed by a 2nd block of 8 hours where the pulse time increased linearly from 1 to 5 seconds.…”
Section: Multiplex M Catarrhalis Antibody Assaymentioning
confidence: 99%
“…Briefly, after used [19]. The uspA2, uspA2H and uspA1 screening primers are situated at the 3'-end of the respective genes, whilst the hag/mid primers amplify a region at the 5'-end of the gene, including a small region of the promotor.…”
Section: Multiplex M Catarrhalis Antibody Assaymentioning
confidence: 99%
See 1 more Smart Citation